Evaluasi Faktor Penyebab Keterlambatan Bongkar Muat Batubara dan Strategi Penanganannya pada PT. Bahtera Adhiguna Cabang Merak: Penelitian - Dafid Ginting; Valar Ariano Simbolon (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Weather conditions play a crucial role in determining the safety and efficiency of ship bunkering operations. This study examines the influence of weather factors on ship bunkering activities conducted by PT Subsea Lintas Globalindo Surabaya. Historical weather data and bunkering operational data were analyzed to identify correlations between weather conditions—such as wind speed, wave height, and rainfall—and bunkering completion time, accident risk, and potential fuel spill incidents. In addition, this study investigates the impact of adverse weather on operational costs and bunkering schedules within the company. The research employed a qualitative approach through field research, including direct observation and interviews with operational personnel, complemented by library research to support theoretical analysis. The results indicate that high wind speeds and significant wave heights negatively affect bunkering completion time, increase the risk of off-hire events, and potentially cause damage to bunkering equipment. Furthermore, heavy rainfall contributes to reduced visibility, which in turn slows down bunkering operations and increases the likelihood of occupational accidents. Overall, the findings emphasize the importance of effective weather risk management to enhance operational safety, efficiency, and cost control in ship bunkering activities.